Changing Covenants in Samoa? From Brothers and Sisters to Husbands and Wives?. Issue 1 (March 2015) - Latai, Latu; Taylor, John P.; Morgain, Rachel
Abstract This article explores how in the process of Christian conversion in Samoa by the London Missionary Society, the indigenous sacred covenant between brother and sister was transposed onto the relation between the pastor, his wife, and the congregation. I consider how far Victorian models of gender and domesticity, based on more individuated modes of personhood and the nuclear family, were promoted by foreign missionaries and whether Samoan people accepted, resisted, and transformed these models. In Samoa, women had assumed powerful statuses as feagaiga 'covenants' and as tamasa 'sacred child'. These ascriptions gave Samoan women sacred power and they were highly esteemed in their families and natal villages. What impact would Christian conversion have on this high valuation of Samoan women? And how would this transformation impact on Samoan ideas about gender and personhood?